The effect of applying sewage sludge on growth and biomass production of Populous nigra L. - رجب يارا; روز القبيلي (Latakia University Journal -Biological Sciences Series, 2025)
The safe disposal of sewage sludge is one of the main environmental concerns around the world, and methods of disposal vary from pumping it to sanitary landfills or incinerating it. However, reusing it as fertilizer that enriches and improves soil properties is considered the best option from an environmental and agricultural point of view due to its richness in essential nutrients for plant growth and development. However, it must be applied with caution to avoid the potential transfer of heavy metals and pathogens into the food chain, and as an alternative solution sludge has been applied as a fertilizer for particularly fast-growing forest species. The aim of this study is to evaluate the effects resulting from applying different doses of dry sewage sludge on the early growth of black poplar. After 7 months of planting, 4 experimental treatments were compared: T0 without adding sludge, T1 (15% sludge), T2 (30% sludge), T3 (60% sludge). The results showed an increase in height over time in all treatments, but at a significantly higher rate in treatments A and B. It was also observed that the diameter increased over the months and a clear moral superiority of treatment an over the rest of the treatments emerged. The results of dry biomass showed superiority of treatments A and B over the rest of the treatments